Education and research in land utilization and application of agrochemicals in Malaysian agriculture - Mohamad, Rosli; Abd. Raffar, Khalip (1990)
Agriculture remain as one of the important sectors in the Malaysian's economy. Through the national agricultural policy, special incentives are provided to ensure continuous growth and development of the agriculture sector. Efficient resourse utilization, social and institutional development are among the objectives of Malaysians Agricultural Policy. Problems relating to the efficient utilization and conservation of agricultural lands and the environment have long been recognised. Appropriate measures have been adopted to minimise the problems. Modern technologies together with strong emphasis on education and research may provide avenues for greater efficiency in the utilization of resources. Formal and non-formal education are regularly conducted to upgrade the knowledge as well as to satisfy the trained manpower needs. Research programs at specialized research institutions and universities provide both short and long term solutions to these problems as well as providing avenues into the new frontiers.